PERAN KEBERTUHANAN SEBAGAI FITRAH DALAM MENGATASI KRISIS IDENTITAS REMAJA - Febrianti Amin; Fauziyah Rahmawati; Firyal Dhia Nailah Junjunan; Mohammad Tsaqif; Abdul Fadhil (Cahaya Ilmu Bangsa Institute, 2024)
This article seeks to examine the Role of Godhead as Fitrah in Overcoming the Adolescent Identity Crisis, where individuals often face identity crises that can affect their psychological and social well-being. Divinity, as an aspect of human nature, plays an important role in helping adolescents overcome this crisis. Through understanding and practicing spiritual values, adolescents can find the meaning of life, goals, and clear directions, so that they are able to form a strong and positive identity. This article discusses the role of divinity in the process of forming adolescent identity, with reference to various relevant research and literature. It is hoped that this understanding can be a reference for educators, parents, and the community in supporting the development of healthy adolescent identities based on spiritual values..